Arab Countries in Transition : An Update on Economic Outlook and Key Challenges. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
Despite uneven progress, there are early signs of improvement and macroeconomic stabilization in some Arab Countries in Transition (ACTs). 1 However, persistently weak growth and subdued private investment amid heightened regional insecurity continue to weigh on the task of reducing unemployment. This calls for accelerated reform efforts by the authorities to achieve higher, more inclusive, and more private sector-led growth, supported by external partners. In addition, mobilizing affordable external financing could help boost well-implemented public investment and provide a short-term impetus to growth and employment, thereby stabilizing difficult socio-political conditions on the ground and providing space for deeper structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet